Comparison of SAME verses CIMT on upper-limb functions in chronic stroke: A Pilot Randomized Control Trial - Shoukat, Alina; Misbah Ghous; Waris, Misbah; Nawaz Malik, Arshad (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the effects of Same Arm Movement Therapy versus Constraint Induced Movement Therapy in improving upper-limb functions in patients of chronic stroke. Method: The pilot, assessor-blind, randomised control trial was conducted from February to September 2020 at the Spine and Physiotherapy Rehab Centre, Riphah Rehabilitation Centre, Lahore, Pakistan, and comprised patients of either gender aged 30-60 years having any type of stroke for a minimum 3 months. They were randomised into group A which received same arm movement therapy for 8 weeks of mental rehearsal of upper limb movements during 45min supervised sessions three times a week and structured independent sessions twice a week, and group B which received constrain induced movement therapy for eight weeks of daily intensive training of the affected extremity for two hours per day, five days per week for eight weeks in association with restriction of the non-affected extremity for 10 hours a day. Measurements were taken at baseline and post-intervention. Data was analysed using SPSS 21. Results: Of the 22 patients, 5(22.7%) were male and 17(77.3%) were female. The average age in group A was 54.91±5.89 years compared to 53.18±6.61 years in group B. All 22(100%) patients had ischemic stroke. Intragroup comparisons showed significant progress in both groups (p<0.05), but intergroup comparisons showed non-significant differences (p>0.05). Conclusion: Both the study interventions had similar effect on upper limb functions among chronic stroke patients. Key Words: Stroke, Therapy, Upper limb, Functions, CIMT, SAME. Iranian Registry of Clinical Trials RCT20200620047848N1 https://www.irct.ir/trial/49054